1978
DOI: 10.1007/bf00581579
|View full text |Cite
|
Sign up to set email alerts
|

Parotid acinar cells: ionic dependence of acetylcholine-evoked membrane potential changes

Abstract: Segments of mouse parotid were placed in a superfusion chamber. Surface acini were impaled by one or two micro-electrodes for measurement of membrane potential and resistance. The acinus under investigation was stimulated by micro-iontophoretic application of acetylcholine (ACh) or adrenaline. Neighbouring acinar cells were electrically coupled. Electrical coupling between acinar cells only occurred within restricted domains probably corresponding to an acinus or a group of acini. Passing direct current throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
27
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 27 publications
9
27
0
Order By: Relevance
“…ROBERTS et al (1978) have shown that methylsulphate substitution for Clr resulted in a shift of EAch from -63 to -77 mV. Therefore, in the absence of Cl-, A23187-evoked major current carriers must be K+ ions through the large K+ channels, which have been found in the parotid acinar cells (MARUYAMA et al, 1983a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROBERTS et al (1978) have shown that methylsulphate substitution for Clr resulted in a shift of EAch from -63 to -77 mV. Therefore, in the absence of Cl-, A23187-evoked major current carriers must be K+ ions through the large K+ channels, which have been found in the parotid acinar cells (MARUYAMA et al, 1983a).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when two channels are activated by the agonist, the reversal potential for the agonist-evoked current response must be at potentials between two equilibrium potentials (Eg and E01), as shown in Fig. 1 B. The reversal potential of -63 mY for the ACh-evoked voltage response in mouse parotid gland acinar cells (RoBERTS et al, 1978) could be explained by postulating the agonist-evoked inward and outward currents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of ACh seems therefore most likely to be due to an effect on the basolateral membrane. The fact that ACh did not change the mean value of the membrane potential is not surprising since in the parotid EACh is at the value of Em (Roberts et al 1978).…”
Section: Pmentioning
confidence: 99%
“…In the parotid gland secretion is associated with a particularly dramatic enhancement of luminal membrane area due to the insertion of granule membrane (Amsterdam, Ohad & Schramm, 1969); electrophysiological experiments were therefore 81P PROCEEDINGS OF THE carried out on superfused segments of mouse parotid as previously described (Roberts, Iwatsuki & Petersen, 1978).…”
Section: Pmentioning
confidence: 99%